2000
DOI: 10.1109/20.908490
|View full text |Cite
|
Sign up to set email alerts
|

Co-Ni-Fe write heads with a 10-μm yoke length for high-speed recording

Abstract: We have developed a Co-Ni-Fe write head with a short yoke length for high-speed recording. By reducing the yoke length to 9 5 m, the eddy currents induced in a yoke with a relatively low resistivity (0 2 m) were reduced. The head of this short yoke had good write performance for a medium with a coercivity of 400 kA/m (5000 Oe) at frequencies up to 250 MHz (the overwrite less than 30 dB, and nonlinear transition shift less than 7%).Index Terms-Eddy currents, highmaterial, high-speed recording, short yoke length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This film has bcc-fcc mixed crystalline structure, and therefore, it is suggested that crystal grains with different crystalline structure from each other act as the inhibitor. Moreover, new heads using these high-B s CoNiFe films show superior write performance compared with heads using conventional magnetic thin films [28,30,55,56]. Therefore, some researchers have reported soft magnetic CoNiFe film with high resistivity.…”
Section: Conife Alloy Filmsmentioning
confidence: 95%
“…This film has bcc-fcc mixed crystalline structure, and therefore, it is suggested that crystal grains with different crystalline structure from each other act as the inhibitor. Moreover, new heads using these high-B s CoNiFe films show superior write performance compared with heads using conventional magnetic thin films [28,30,55,56]. Therefore, some researchers have reported soft magnetic CoNiFe film with high resistivity.…”
Section: Conife Alloy Filmsmentioning
confidence: 95%
“…Figure 1 is a schematic drawing of a shielded loop coil, which is the detection part of the magnetic field probe. The coil of our new probe was fabricated on a glass substrate by using a thin-film process called fine pattern-plating 8) . In the lithographic process, reduction projection printing using an i-line stepper was used instead of the contact printing used to fabricate our previous coil on a glass substrate.…”
Section: Structure Of a Shielded Loop Coilmentioning
confidence: 99%
“…This B s value is higher than that of any other CoNiFe‐based soft magnetic thin film which had been developed in 1997. In addition, the CoNiFe plating bath was further improved, and the CoNiFe film plated from the improved bath was used for fabricating commercial quality recording heads,16–20 as shown in Figure 2, where CoNiFe film as thick as 1.5 µm was uniformly deposited without the formation of voids or cracks even upon bending. The corrosion characteristics of CoNiFe are also represented and summarized in Reference 17.…”
Section: Creation Of Magnetic Thin Films For Magnetic Recording Drivesmentioning
confidence: 99%